The unmet treatment need of traumatized anterior teeth in selected secondary school children in Ibadan, Nigeria (2009)
Abstract – Treatment of traumatized anterior teeth is highly desirable to relieve pain, maintain esthetics and to preserve the balance of the anterior part of the mouth; however many may go untreated. The aim of this study was to assess the prevalence of damage to permanent anterior teeth in school adolescents, the average duration of trauma and to ascertain the level of the unmet treatment need. A total of 1532 secondary school children between the ages 12 and 19 years participated in the study. They were randomly selected from public secondary schools in ﬁve local government areas in Ibadan using a multistage sampling method. Participants were examined with the aid of mouth mirrors and probes under natural light. Traumatic anterior dental injuries were recorded by the same investigator (DMA) according to WHO classiﬁcation. One hundred and sixty-ﬁve participants sustained injuries to their anterior teeth. Their mean age was 15.47 ± 2.09 years, with a male to female ratio of 1.5:1. The commonest cause was fall (78.8%) with road trafﬁc accident being the least (1.8%). The tooth most commonly injured is the upper left incisor (48.0%) closely followed by upper right central (43.1%). Enamel fracture was seen in 46.5% and enamel–dentine in 42.6% of the traumatized teeth. Most (79.4%) of the children sustained injury to one tooth only. Of the participants, only 30 (18.2%) had previous dental consultation while only nine (5.5%) consulted the dentist following the trauma; however, none of the teeth had any form of restoration. Average time elapsed between trauma and dental examination was about 3.5 years. Many participants had had injury for about 2 years before dental examination. In conclusion, there is a high unmet treatment need of traumatized anterior teeth in the study population.